Compliance management a how-to guide for executives, lawyers, and other compliance professionals - Singh, Nitish 1972-; Bussen, Thomas J. (Praeger, 2015)
"This practical guide shows how to build an effective compliance and ethics program that will lower a business's risks and improve productivity"..
Includes bibliographical references (pages 213-245) and index
Keywords: BUSINESS & ECONOMICS / Human Resources & Personnel Management; Recht; Wirtschaft; Corporate governance -- Law and legislation -- United States; Commercial law -- United States; Business ethics -- United States; USA